Towards the Prediction of Micro-EDM Drilling Performance on WC Varying the Hole Depth - D'Urso, Gianluca; Quarto, Mariangela; Pellegrini, Giuseppe; Ravasio, Chiara (Manufacturing Technology Journal, 2018)
The present work deals with the execution of through micro-holes on tungsten carbide plates using a micro-EDM (Electrical Discharge Machining) machine. The investigation focuses on the monitoring of the performance during the drilling phase in order to obtain the in progress behavior of the performance indexes. The experiments were carried out by varying some process parameters such as peak current, voltage and frequency to achieve both high and low power discharge conditions. Regarding electrodes, the most commonly industrial used ones were selected: tubular tungsten carbide and brass. The performance indexes taken into account were machining time, Material Removal Rate (MRR), Tool Wear (TW) and Tool Wear Ratio (TWR). Brass electrode always resulted to be the best solution in terms of drilling speed even though the wear of this electrode type is remarkable higher than the tungsten one. The evolution of the performance indexes during the drilling operation showed the same trend for both electrodes: increasing the hole depth, the drilling operation proceeds in a more difficult way, due to the evacuation of debris that becomes more difficult and therefore the performance indexes get worse. Finally, the technology windows of the cumulated MRR and TWR were defined for both electrode materials, in order to predict the micro EDM process performance varying the hole depth.
Keywords: Micro-EDM; Tungsten carbide; Micro-drilling; Process performance; Prediction ability